Two-Metal-Ion Catalysis: Inhibition of DNA Polymerase Activity by a Third Divalent Metal Ion - Wang, Jimin; Konigsberg, William H. (Frontiers in Molecular Biosciences, 2022)
Almost all DNA polymerases (pols) exhibit bell-shaped activity curves as a function of both pH and Mg2+ concentration. The pol activity is reduced when the pH deviates from the optimal value. When the pH is too low the concentration of a deprotonated general base (namely, the attacking 3'-hydroxyl of the 3' terminal residue of the primer strand) is reduced exponentially. When the pH is too high the concentration of a protonated general acid (i.e., the leaving pyrophosphate group) is reduced. Similarly, the pol activity also decreases when the concentration of the divalent metal ions deviates from its optimal value: when it is too low, the binding of the two catalytic divalent metal ions required for the full activity is incomplete, and when it is too high a third divalent metal ion binds to pyrophosphate, keeping it in the replication complex longer and serving as a substrate for pyrophosphorylysis within the complex. Currently, there is a controversy about the role of the third metal ion which we will address in this review.